Localization of the gangliosides GD2 and GD3 in adhesion plaques and on the surface of human melanoma cells. - Cheresh, D A (1984)
The predominant gangliosides produced by two cultured human melanoma cell lines are GD3 and/or GD2. These gangliosides were found to be cell associated and present in substratum-attached material after cell removal by EDTA. Monoclonal antibodies directed to GD2 and GD3 specified the cell-surface distribution of these gangliosides and localized them in focal adhesion plaques at the interface of cells and their substratum. These attachment sites did not represent indiscriminant membrane fragments remaining after removal of cells with EDTA, because neither melanoma-associated proteoglycan nor class I histocompatibility antigens were detected by their respective antibodies. Our data suggest that the disialogangliosides GD2 and GD3 may be involved in the interaction between human melanoma cells and solid substrata.